1990
DOI: 10.1002/1097-0142(19901101)66:9<1873::aid-cncr2820660904>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Final report of the french multicenter phase II study of the nitrosourea fotemustine in 153 evaluable patients with disseminated malignant melanoma including patients with cerebral metastases

Abstract: One hundred sixty-nine patients with histologic evidence of disseminated malignant melanoma, including patients with cerebral metastases, were entered into a Phase II study of the nitrosourea fotemustine. The treatment regimen consisted of a 100 mg/m2 1 hour IV infusion every week for 3 consecutive weeks, followed by a 4- to 5-week rest period (induction therapy). In responding or stabilized patients, maintenance therapy consisted of 100 mg/m2 every 3 weeks until the disease progressed. One hundred fifty-three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
70
0
5

Year Published

1993
1993
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 223 publications
(77 citation statements)
references
References 8 publications
2
70
0
5
Order By: Relevance
“…However, the two cases of interstitial pneumonitis in our study received a cumulative dosage of < 400 mg m-2 of fotemustine suggesting that the synergy between DTIC and fotemustine (as used in the schedule here) may be responsible for the acute pulmonary event, possibly related to greater cytotoxicity in normal lung cells following depletion of the endogenous ATase. A recent phase II study of fotemustine alone in 153 patients with disseminated melanoma was not associated with any pulmonary toxicity and similar finding was reported in another 38 patients with gliomas treated with fotemustine alone (Jacquillat et al, 1990;Frenay et al, 1991). Lung tissue has a relatively low ATase activity in comparison with other tissues (Grafstrom et al, 1984;Gerson et al, 1986) and as a result they may be more sensitive to the cytotoxic effects of DNA alkylation.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…However, the two cases of interstitial pneumonitis in our study received a cumulative dosage of < 400 mg m-2 of fotemustine suggesting that the synergy between DTIC and fotemustine (as used in the schedule here) may be responsible for the acute pulmonary event, possibly related to greater cytotoxicity in normal lung cells following depletion of the endogenous ATase. A recent phase II study of fotemustine alone in 153 patients with disseminated melanoma was not associated with any pulmonary toxicity and similar finding was reported in another 38 patients with gliomas treated with fotemustine alone (Jacquillat et al, 1990;Frenay et al, 1991). Lung tissue has a relatively low ATase activity in comparison with other tissues (Grafstrom et al, 1984;Gerson et al, 1986) and as a result they may be more sensitive to the cytotoxic effects of DNA alkylation.…”
Section: Discussionmentioning
confidence: 54%
“…bolus or daily injections over 5 days, have produced an overall response rate of about 20% (Comis 1976;Mastrangelo et al, 1982;Geeraerts & Nathanson, 1986;Balch et al, 1989) 800 mg m-2 with dactinomycin (Hochster et al, 1985) or 250 mg m-2 daily for 5 days with dactinomycin (Robidoux et al, 1982) gave response rates of 23%, 22% and 15% respectively. Fotemustine alone gave a response rate of about 24% (Jacquillat et al, 1990). Therefore the overall response rate of 30% achieved with the current study would support the use of a combination of DTIC and fotemustine, although, because of the absence of a direct comparison, no conclusions about the scheduling can be reached.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…The response rates of brain metastases to fotemustine as single agent in Phase II studies ranged between 8% and 28%. [21][22][23][24] However, in a recent, large, Phase III study that compared fotemustine with dacarbazine in patients with metastatic melanoma, the response of brain metastases was 5.9% after treatment with fotemustine versus 0% after dacarbazine. 21 Anecdotal responses also were reported after other cytotoxic regimens, predominantly in patients with favorable characteristics like solitary, small, or asymptomatic brain metastases.…”
Section: Toxicitymentioning
confidence: 99%
“…Trials of a related compound, fotemustine, have reported response rates of 5 -25% in melanoma metastatic to the brain (Jacquillat et al, 1990;Mornex et al, 2003;Avril et al, 2004) and fotemustine has also been given in combination with dacarbazine Merimsky et al, 1992;Lee et al, 1993;Chang et al, 1994;Comella et al, 1997;Richard et al, 1998;Seeber et al, 1998) and with temozolomide (Marzolini et al, 1998;Gander et al, 1999). These drug combinations are generally well tolerated although unexpected pulmonary toxicity was reported in two studies of the combination of dacarbazine and fotemustine (Gerard et al, 1993;Lee et al, 1993).…”
mentioning
confidence: 99%